Multisensory gamma stimulation mitigates the effects of demyelination induced by cuprizone in male mice - Daniela Rodrígues-Amorím; P. Lorenzo Bozzelli; TaeHyun Kim; Liwang Liu; Oliver Gibson; Cheng-Yi Yang; Mitchell H. Murdock; Fabiola Galiana-Melendez; Brooke Schatz; Alexis Davison; Md. Rezaul Islam; Dong Shin Park; et al. (2024)
Demyelination is a common pathological feature in a wide range of diseases, characterized by the loss of myelin sheath and myelin-supporting oligodendrocytes. These losses lead to impaired axonal function, increased vulnerability of axons to damage, and result in significant brain atrophy and neuro-axonal degeneration. Multiple pathomolecular processes contribute to neuroinflammation, oligodendrocyte cell death, and progressive neuronal dysfunction. In this study, we use the cuprizone mouse model of demyelination to investigate long-term non-invasive gamma entrainment using sensory stimulation as a potential therapeutic intervention for promoting myelination and reducing neuroinflammation in male mice. Here, we show that multisensory gamma stimulation mitigates demyelination, promotes oligodendrogenesis, preserves functional integrity and synaptic plasticity, attenuates oligodendrocyte ferroptosis-induced cell death, and reduces brain inflammation. Thus, the protective effects of multisensory gamma stimulation on myelin and anti-neuroinflammatory properties support its potential as a therapeutic approach for demyelinating disorders.